Antibacterial Compound from n-Hexane Fraction of Dillenia ochreata Leaves - Heni Yohandini; Muharni Muharni; Putra Setia Aji Candra (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
Semprawang (Dillenia ochreata) belongs to the Dilleniaceae family that has been used by the Musi tribe, Banyuasin, South Sumatra, for scurvy medicine. This study aims to isolate secondary metabolites from D. ochreata leaves n-hexane extract and test their antibacterial activity against Escherichia coli and Staphylococcus aureus. The D. ochreata leaves were extracted through the maceration method with n-hexane solvent, and the isolated compounds were purified using column chromatography. The isolated compounds were analyzed using FT-IR, 1H-NMR, and 13C-NMR spectroscopy and compared the spectroscopic data with the literature. The antibacterial activity was determined against the E. coli and S. aureus bacteria with the disc diffusion method and MIC value was determined by the microdilution method. Based on the analysis of the spectroscopic data and compared with literature data, it is suggested that the isolated compounds are 3Î²-glucopyranosyl-lup-20(29)-en-28-oic, which mixes with aromatic compound. The isolated compounds showed antibacterial activity with a minimum inhibitory concentration (MIC) to E. coli at 120 Âµg/mL and S. aureus at 60 Âµg/mL